(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
Today, X-ray machines have not lost their relevance in diagnosis and treatment. X-rays are not available, especially in the diagnosis of lung disease, bone fractures and dental disease. Without this type of research, a person can only be miraculously healed. X-rays allow to obtain a very good graphical image of anatomical structures. This will help to make an accurate diagnosis and prescribe treatment. In medicine, the indications for radiography are to diagnose various diseases, to determine the shape of these organs, their location, the condition of the mucous membranes and peristalsis.Our main goal is to consider the benefits, harms and, of course, the disadvantages of X-rays